Parental gonadossomatic mosaicism in HIVEP2-related intellectual disability and impact on genetic counseling–case report - Abreu, Maria; Branco, Tiago; Figueiroa, Sónia; Reis, Cláudia Falcão (Frontiers in Genetics, 2023)
Intellectual development disorder, autosomal dominant 43 (MRD43) is an autosomal dominant disorder caused by heterozygous mutations in the HIVEP2 gene. In this report, we describe the case of a 4-year-old boy with global development delay, hypotonia and dysmorphic features, in whom the finding of a heterozygous nonsense pathogenic variant in exon 5 of HIVEP2 [c.2827C>T p. (Arg943*)] through WES established a MRD43 diagnosis. Our patient’s phenotype overlaps with other MRD43 descriptions in the literature. Unlike previously reported cases, where the condition was de novo, the healthy mother presented mosaicism for the pathogenic variant. Thus, the recurrence risk increased significantly from 1% to up to 50%. The description of a variant inherited for MDR43 is singular in the literature and this description highlights the importance of parental studies for accurate genetic counselling, particularly for family planning.